EXPERIMENTAL STUDY OF FLOW THROUGH TRAPEZOIDAL WEIR CONTROLLED UNDER A SEMI-CIRCULAR GATE (FUDMA JOURNAL OF SCIENCES, 2021)
Different parameters of a weir model have a great effect on the discharge coefficient. In this experimental study the effect of varying angle of a trapezoidal weir coupled with a below semi-circular gate is determined. The result showed that the higher the value of  the higher the coefficient of discharge. The respective average discharge coefficient  of the block model and the trapezoidal weir models are; 0.48031,0.48880, 0.49565, 0.49647, 0.49892 and 0.49934. As such the trapezoidal weir with   has the highest value of average discharge coefficient =0.49934. Hence the most efficient. Linear and nonlinear regression analysis were used to generate mathematical equations that can be used to predict the flow rate Q for the combined weir-gate structure and the discharge coefficient  of the most efficient model with  respectively. The discharge coefficient for the most efficient weir model was found to be 3.81% more than that of the block model (with rectangular weir). The predicted coefficient of discharge   for the most efficient model was also found to be in good agreement with the observed discharge coefficient with a percentage error in the range of  0.4%
Keywords: coefficient of discharge, weir angle, trapezoidal weir